2003
DOI: 10.1021/la034146y
|View full text |Cite
|
Sign up to set email alerts
|

Size-Selective Synthesis of Cubooctahedral Palladium Particles Mediated by Metallomicelles

Abstract: The reduction of [PdCl4]2- by hydrazine in the postmicellar region of even-numbered alkyltrimethylammonium bromides C n TABr (with n = 8 to 16) yielded fairly monodisperse Pd particles with mean diameters in the range 1.6−6.8 nm. Transmission electron microscopy (TEM) measurements indicated that the particle size decreases with increasing length of the alkyl chain, decreasing precursor concentration, and decreasing surfactant concentration. Kinetic measurements demonstrated that the nucleation is a fast proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 65 publications
4
53
0
1
Order By: Relevance
“…It may therefore be concluded that the amount of organic residues on the surface of the Pd particles was insignificant. The above synthesis method afforded organophilic Pd-M samples with the same Pd content, differing only in the mean crystallite diameter and the size distribution of the Pd particles [20,21]. The Pd contents of the samples Pd-M1, Pd-M2 and Pd-M3, which were subjected to further investigations, were 0.15 ± 0.01%, as confirmed by ICP-AES measurements (Jobin Yvon 24 spectrometer, λ = 229.7 and 324.3 nm).…”
Section: Methodsmentioning
confidence: 99%
“…It may therefore be concluded that the amount of organic residues on the surface of the Pd particles was insignificant. The above synthesis method afforded organophilic Pd-M samples with the same Pd content, differing only in the mean crystallite diameter and the size distribution of the Pd particles [20,21]. The Pd contents of the samples Pd-M1, Pd-M2 and Pd-M3, which were subjected to further investigations, were 0.15 ± 0.01%, as confirmed by ICP-AES measurements (Jobin Yvon 24 spectrometer, λ = 229.7 and 324.3 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Thereby, the liquid chemistry such as pH value will be changed by the plasma irradiation, which can influence the rate and probability of chemical reactions in liquid, that we must pay attention if we want to elaborately control the synthesis. Interestingly, hydrazine (N2H4) has been observed after an exposure of N2 and CO2 [96] or Ar/ammonia [97] plasma on water, and Pd [98] Anodic dissolution has been used for electrochemical synthesis of Pd [100] and Ag [101] NPs, and gold nanorods [102], anodic dissolution can also take place in the PLIs since the plasma-liquid system is actually a modified electrochemical cell [15,103]. While just a few studies considered the effect of anodic dissolution in the NP synthesis from the PLIs [46,69].…”
Section: Plasma Over Liquidmentioning
confidence: 99%
“…Pd nanocrystals with diverse morphologies have been synthesized, including wires [13], spheres [14], tubes [15], cubes [16], plates [17], rods [18][19][20], tetrahexahedra [21], cubooctahedra [22], octahedra [23], tetrahedra [24], and concave tetrahedra [25]. Among various shapes, {100}-enclosed Pd nanocubes are of particular interest in relation to formic acid oxidation because the {100} facet of Pd shows the highest catalytic activity among the three lowindex facets (Pd{100} > Pd{111} > Pd{110}) [26].…”
Section: Introductionmentioning
confidence: 99%